Deep LOFAR observations of the merging galaxy cluster CIZA J2242.8+5301. Issue 1 (30th June 2017) - Hoang, D. N.; Shimwell, T. W.; Stroe, A.; Akamatsu, H.; Brunetti, G.; Donnert, J. M. F.; Intema, H. T.; Mulcahy, D. D.; Röttgering, H. J. A.; van Weeren, R. J.; Bonafede, A.; Brüggen, M.; et al.
Abstract: Previous studies have shown that CIZA J2242.8+5301 (the 'Sausage' cluster, z = 0.192) is a massive merging galaxy cluster that hosts a radio halo and multiple relics. In this paper, we present deep, high-fidelity, low-frequency images made with the LOw-Frequency Array (LOFAR) between 115.5 and 179 MHz. These images, with a noise of 140 μJy beam − 1 and a resolution of θbeam = 7.3 arcsec × 5.3 arcsec, are an order of magnitude more sensitive and five times higher resolution than previous low-frequency images of this cluster. We combined the LOFAR data with the existing Giant Metrewave Radio Telescope (GMRT) (153, 323, 608 MHz) and Westerbork Synthesis Radio Telescope (WSRT) (1.2, 1.4, 1.7, 2.3 GHz) data to study the spectral properties of the radio emission from the cluster. Assuming diffusive shock acceleration (DSA), we found Mach numbers of $\mathcal {M}_{n}=2.7{}_{-0.3}^{+0.6}$ and $\mathcal {M}_{s}=1.9_{-0.2}^{+0.3}$ for the northern and southern shocks. The derived Mach number for the northern shock requires an acceleration efficiency of several percent to accelerate electrons from the thermal pool, which is challenging for DSA. Using the radio data, we characterized the eastern relic as a shock wave propagating outwards with a Mach number of $\mathcal {M}_{e}=2.4_{-0.3}^{+0.5}$, which is in agreement with $\mathcal {M}_{e}^{X}=2.5{}_{-0.2}^{+0.6}$ that we derived from Suzaku data. The eastern shock is likely to be associated with the major cluster merger. The radio halo was measured with a flux of 346 ± 64 mJy at 145 MHz. Across the halo, we observed a spectral index that remains approximately constant ($α ^{\text{145 MHz-2.3 GHz}}_{\rm {across \sim 1\ Mpc}^2}=-1.01± 0.10$ ) after the steepening in the post-shock region of the northern relic. This suggests a generation of post-shock turbulence that re-energies aged electrons.